Complete genome sequence of Serratia plymuthica strain AS12. Issue 2 (March 2012) - Neupane, Saraswoti; Finlay, Roger; Alström, Sadhna; Goodwin, Lynne; Kyrpides, Nikos; Lucas, Susan; Lapidus, Alla; Bruce, David; Pitluck, Sam; Peters, Lin; Ovchinnikova, Galina; Chertkov, Olga; et al.
Abstract A plant-associated member of the familyEnterobacteriaceae, Serratia plymuthica strain AS12 was isolated from rapeseed roots. It is of scientific interest because it promotes plant growth and inhibits plant pathogens. The genome ofS. plymuthica AS12 comprises a 5, 443, 009 bp long circular chromosome, which consists of 4, 952 protein-coding genes, 87 tRNA genes and 7 rRNA operons. This genome was sequenced within the 2010 DOE-JGI Community Sequencing Program (CSP2010) as part of the project entitled "Genomics of four rapeseed plant growth promoting bacteria with antagonistic effect on plant pathogens".